Pengembangan METABUL (Media Tangkas Operasi Bilangan Bulat) untuk Melatih Kemampuan Berpikir Kreatif Siswa Kelas 7 - Siregar, Alfi Syahrin; Dewi, Aulia Rahma; Liyusriha, Ifaqoti; Pramesti, Sifaroh Efria; Rofiki, Imam (Jurnal Tadris Matematika, 2024)
Using manipulative media can help children who are having trouble learning mathematics. In addition to simplifying the learning process, this manipulative media helps pupils develop their capacity for original thought. Creative thinking abilities are crucial because it inspire students to try different approaches to addressing problems, promotes creativity, and raises their level of involvement in class activities. Despite the significance of creative thinking abilities, prior studies have shown that Indonesian students still need to improve their levels of these capabilities, particularly regarding integer operations. Thus, to fill this gap, this research developed Media Tangkas Operasi Bilangan Bulat (METABUL). This media used the ADDIE paradigm in research and development (R&D) to stimulate students' capacity for creative thinking. Interview guidelines, learning media validation questionnaires, and teacher and student response questionnaires are the data collection instruments used in this research. The research participants were six class VII junior high school students in Malang City with three validators (one practitioner and two experts). Research findings show that developing METABUL manipulative media has a high level of validity of 93.17% and a good response from teachers at 86% and students at 87.41%.